Perencanaan Kebutuhan Pendinginan Udara Auditorium Universitas Ivet - Suyanto Suyanto; Riyanto Wibowo (Marine Science and Technology Journal, 2020)
The need for air cooling is currently considered important, especially for cooling meeting rooms and auditoriums. Thus the cool and comfortable air conditions can be presented. This research was conducted to determine the air cooling load in the Ivet University Auditorium. The method used is to calculate the amount of heat that comes from outdoors and indoors. The amount of heat from the room is the heat from the sun's heat that propagates through walls, roofs, glass windows and doors. The heat that comes from inside the room is sourced from humans as occupants, lights, and other electronic equipment. From the results of data analysis it can be determined that the cooling load of Ivet University Auditorium is 11,1100 Watts or equivalent to 379073 Btu / hr. The total AC power needed to cool the room is 42 PK.